ANALISIS PENERAPAN AKUNTANSI KEUANGAN BADAN LAYANAN UMUM DAERAH (BLUD) PADA RUMAH SAKIT UMUM DAERAH (RSUD) ANUNTALOKO KABUPATEN PARIGI MOUTONG - Asfiah, Asfiah (Katalogis, 2017)
The aims of this study are : 1) to determine and analyze the accounting system of public services agency at Anuntaloko Public Hospital in Parigi Moutong; 2) to determine and analyze financial statement of public services agency at Anuntaloko Public Hospital in Parigi Moutong; 3) to determine inhibing and enabling factors ot accounting system of public services agency at Anuntaloko Public Hospital in Parigi Moutong. Type of this study is descriptive qualitative. The result concludes that : 1) the accounting system of public services agency at Anuntaloko Public Hospital in Parigi Moutong is not based on the accounting cycle; 2) financial reporting in Anuntaloko Hospitel has been prepared on the accrual basis in accordance with Government Regulation No. 71 of 2010 while report o9n the financial statements based on SAK still need to be addressed based on the acconting policies of BLUD; 3) enabling factors include supporting facilities and work environment, guidelines or rules on working procedures governing the financial management mechanism of BLUDs, funding programs, as well as the development of technology and information to inprove employee performance, While inhibiting factors include the quality of human resources that is not optimal, lack of commitment and leaders’ direction on the importance of accounting data, inadequate financial operating system (software), and the performance of internal auditor unit has not yet optimal.